2013
DOI: 10.1016/j.immuni.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Prepositioning and Local CXCL9 Chemokine-Mediated Guidance Orchestrate Rapid Memory CD8+ T Cell Responses in the Lymph Node

Abstract: Summary After an infection, the immune system generates long-lived memory lymphocytes whose increased frequency and altered state of differentiation enhance host defense against re-infection. Recently, the spatial distribution of memory cells was found to contribute to their protective function. Effector memory CD8+ T cells reside in peripheral tissue sites of initial pathogen encounter, in apparent anticipation of re-infection. Here we show that within lymph nodes (LN), memory CD8+ T cells were concentrated n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
222
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 185 publications
(231 citation statements)
references
References 58 publications
9
222
0
Order By: Relevance
“…Within a reactive lymph node, the CXCL9-CXCR3 axis plays a role in migration of CD8 1 memory T cells and their interaction with infected macrophages. 10 Similar roles are expected for CXCR3 ligands or other chemokines expressed in inflammatory tissues. ECM fragments, produced by matrix metalloproteinases and other proteases that degrade ECM, can also act as chemoattractants to guide cell migration in inflamed tissues.…”
mentioning
confidence: 72%
“…Within a reactive lymph node, the CXCL9-CXCR3 axis plays a role in migration of CD8 1 memory T cells and their interaction with infected macrophages. 10 Similar roles are expected for CXCR3 ligands or other chemokines expressed in inflammatory tissues. ECM fragments, produced by matrix metalloproteinases and other proteases that degrade ECM, can also act as chemoattractants to guide cell migration in inflamed tissues.…”
mentioning
confidence: 72%
“…It will be interesting to determine whether a similar process is happening with Plasmodium-specific cells in the liver. Moreover, we do not know which GPCRs are required for further T-cell recruitment and cluster formation; interestingly, it has been demonstrated that both specific and nonspecific T cells are recruited to the site of influenza virus infection in the lungs via CCR5 (27), whereas in the lymph node, CXCL9-CXCR3 interactions have been shown to be critical for the clustering of antigen-specific effector CD8 + T cells around DCs in viral infections (11,28).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it was estimated that 6 h of cognate CD8 + T-cell contact were required to induce apoptosis of tumor cells in vivo (6). In studies with vaccinia virus, Leishmania, Listeria, and Toxoplasma, cognate T cells were seen changing their migratory behavior in the presence of microbial antigen, although pathogen killing was not observed (7)(8)(9)(10)(11). In fact, the elimination of a microbe by CD8 + T cells has not been seen in vivo to date, which is surprising given that in vitro studies have suggested that CD8 + T cells are capable of eliminating target cells after ∼5 min of contact (2,12).…”
mentioning
confidence: 99%
“…In a later set of experiments, Kastenmuller et al similarly demonstrated that sc. delivery of the replication-incompetent VACV strain MVA resulted in CXCR3-dependent movement of central memory T cells to the LN's peripheral regions (10). Together, these studies show that antiviral central memory CD8 C T cells are poised to quickly respond and relocate to areas of acute virus infection within LNs.…”
Section: Lymph Nodementioning
confidence: 78%
“…Differences in viral dose as well as the precise viral strain can alter results, particularly if immunomodulatory proteins are deleted. For instance, the priming site of na€ ıve CD8 C T cells differs in LNs of mice infected with 10 6 plaque forming units (pfu) of recombinant vaccinia virus (VACV) versus those infected with 10 8 pfu of a greatly attenuated, replication incompetent strain of VACV known as modified vaccinia Ankara (MVA) (9,10).…”
Section: Introductionmentioning
confidence: 99%